Roles of Gut Microbiota in the Regulation of Hippocampal Plasticity, Inflammation, and Hippocampus-Dependent Behaviors - Tang, Wen; Meng, Zhaoyou; Li, Ning; Liu, Yiyan; Li, Li; Chen, Dongfeng; Yang, Yang (Frontiers in Cellular and Infection Microbiology, 2021)
The study of the gut microbiota-brain axis has become an intriguing field, attracting attention from both gastroenterologists and neurobiologists. The hippocampus is the center of learning and memory, and plays a pivotal role in neurodegenerative diseases, such as Alzheimer’s disease (AD). Previous studies using diet administration, antibiotics, probiotics, prebiotics, germ-free mice, and fecal analysis of normal and specific pathogen-free animals have shown that the structure and function of the hippocampus are affected by the gut microbiota. Furthermore, hippocampal pathologies in AD are positively correlated with changes in specific microbiota. Genomic and neurochemical analyses revealed significant alterations in genes and amino acids in the hippocampus of AD subjects following a remarkable shift in the gut microbiota. In a recent study, when young animals were transplanted with fecal microbiota derived from AD patients, the recipients showed significant impairment of cognitive behaviors, AD pathologies, and changes in neuronal plasticity and cytokines. Other studies have demonstrated the side effects of antibiotic administration along with the beneficial effects of probiotics, prebiotics, and specific diets on the composition of the gut microbiota and hippocampal functions, but these have been mostly preliminary with unclear mechanisms. Since some specific gut bacteria are positively or negatively correlated to the structure and function of the hippocampus, it is expected that specific gut bacteria administration and other microbiota-based interventions could be potentially applied to prevent or treat hippocampus-based memory impairment and neuropsychiatric disorders such as AD.